Analisis Permainan Tradisional Engklek Dalam Meningkatkan Kemampuan Motorik Kasar Di PAUD Ar-Rafizqi - Desi Kusuma Wati; Amat Hidayat; Ibnu Sina; Inten Risna; Ratu Yustika Rini (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze the influence of the traditional game engklek in improving gross motor skills of early childhood learners in Group B at PAUD Ar-Rafizqi. The research was motivated by the decline in children's physical activity due to changes in play patterns, increased screen use, and rising cases of gross motor delays that affect balance, muscle strength, coordination, and school readiness. A descriptive qualitative method was employed with three participants aged 5–6 years. Data were collected through observation, interviews, and documentation conducted over five days of engklek implementation. The results show that consistent engagement in engklek activities significantly improved various aspects of gross motor skills, including strength, balance, agility, coordination, speed, flexibility, and endurance. Two children (MRD and KA) achieved the “Developing as Expected” category, while one child (AAI) reached the “Beginning to Develop” level. These improvements were evident in their ability to hop, throw the gacuk, and maintain balance independently. The findings support previous studies indicating that engklek is an effective and enjoyable learning medium to enhance gross motor development in early childhood. Therefore, traditional games like engklek are recommended as routine activities in early childhood education to support children’s optimal physical development